The changes of antioxidant system and intestinal bacteria in earthworms (Metaphire guillelmi) on the enhanced degradation of tetracycline. (February 2021) - Yin, Bangyi; Zhang, Manrui; Zeng, Yuxiao; Chen, Haowen; Fan, Tianxinzhi; Wu, Zexuan; Cao, Linkui; Zhao, Qi
Abstract: Tetracycline (TC) in soil severely imperils food security and ecosystem function. Metaphire guillelmi is a common species in farmland. It could impact the degradation of antibiotics. However, how it affects is rarely unknown. Hence, the present study aimed to investigate the effects of M. guillelmi on the TC degradation in soil and the changes of the antioxidant system and intestinal bacteria in M. guillelmi. The treatments that M. guillelmi was inoculated on soil contaminated with different TC concentrations were contrasted with those without M. guillelmi. After 21 days, the degradation rate of TC significantly increased by 13.70%, 18.14% and 29.01% at 10, 50 and 100 mg kg −1 TC dose, respectively, due to the inoculation of M. guillelmi . The half-life of TC was also shortened nearly by 1/3 to 2/3. Superoxide dismutase (SOD) increased in a dose-dependent manner with the increase of TC concentration on the 7th and 14th day. Catalase (CAT) and glutathione S-transferase (GST) presented an inverted U-shaped dose response on the 7th day, and the peak of enzyme activities occurred at TC concentration of 0.1, 1 mg kg −1 (CAT) and 0.1 mg kg −1 (GST). Malondialdehyde (MDA) contents did not change significantly. At the phylum level, only Verrucomicrobia significantly decreased under 1 mg kg −1 and 100 mg kg −1 TC dose. Genus Paracoccus, Singulisphaera, Acinetobacter and Bacillus significantly increased and became the dominant bacterium during the TC degradation. Overall, the antioxidant system and intestinal bacteria of M. guillelmi were affected by the different concentrations of TC pollution, which provided new ideas for the research of mechanism of TC degradation by earthworms in the future. Highlights: Metaphire guillelmi significantly accelerated the degradation of TC. SOD, CAT and GST activities were increased, while MDA content was not changed. The dominant bacterium ( Paracoccus, Singulisphaera,   Acinetobacter  and  Bacillus ) significantly increased.